Input of Protein to Lake Water Microcosms Affects Expression of Proteolytic Enzymes and the Dynamics of Pseudomonas spp. - Worm, Jakob (American Society for Microbiology, 2001)
The objective of this study was to determine how an input of protein to lake water affects expression of a proteolytic potential and influences the abundance and composition of a specific group of bacteria. Pseudomonas spp. were chosen as a target group that can be recovered on selective growth media and contain both proteolytic and nonproteolytic strains. Amendment with 2 mg of casein per liter increased total proteinase activity (hydrolysis of [(3)H]casein) by 74%, leucine-aminopeptidase activity (hydrolysis of leucine-methyl-coumarinylamide) by 133%, bacterial abundance by 44%, and phytoplankton biomass (chlorophyll a) by 39%. The casein amendment also increased the abundance of culturable Pseudomonas spp. by fivefold relative to control microcosms but did not select for proteolytic isolates. Soluble proteins immunochemically related to the Pseudomonas fluorescens alkaline proteinase, AprX, were detected in amended microcosms but not in the controls. The expression of this class of proteinase was confirmed exclusively for proteolytic Pseudomonas isolates from the microcosms. The population structure of Pseudomonas isolates was determined from genomic fingerprints generated by universally primed PCR, and the analysis indicated that casein amendment led to only minor shifts in population structure. The appearance of AprX-like proteinases in the lake water might thus reflect a general induction of enzyme expression rather than pronounced shifts in the Pseudomonas population structure. The limited effect of casein amendment on Pseudomonas population structure might be due to the availability of casein hydrolysates to bacteria independent of their proteinase expression. In the lake water, 44% of the total proteinase activity was recovered in 0.22-μm-pore-size filtrates and thus without a direct association with the bacteria providing the extracellular enzyme activity. Since all Pseudomonas isolates expressed leucine-aminopeptidase in pure culture, proteolytic as well as nonproteolytic pseudomonads were likely members of the bacterial consortium that metabolized protein in the lake water.